Governing Transnational Commons: How International Treaties and Multi‐Stakeholder Organizations Shape Cooperation and Conflict - Joshi, Amol M.; Antons, David; Piening, Erk P.; Dienhart, Christina; Salge, Torsten‐Oliver (Journal of Management Studies, 2024)
AbstractWhen common‐pool resources such as freshwater, clean air, and fisheries span national borders, the collective action problems encountered are particularly severe. This study explores the role of polycentric governance systems in overcoming these pressing problems, which frequently underlie global grand challenges. Integrating political economy and management research, we hypothesize about how two governance mechanisms – international treaties and multi‐stakeholder organizations – shape the likelihood of cooperation and conflict between countries. Leveraging unique, longitudinal data capturing interactions of countries bordering international river basins, our empirical analysis reveals two main findings. First, we find that the specification of multi‐stakeholder organizations enhances water‐related cooperation and reduces water conflict among countries, while the specification of international treaties enhances cooperation but does not affect conflict. Second, we find that leaving one of these governance mechanisms less specified than the other actually improves, rather than harms, relationships between countries. Our findings point to a superior governance configuration that simultaneously enhances cooperation and constrains conflict. This configuration combines: (1) treaties that establish property rights but leave procedural rules and uncertainty management provisions less established with (2) multi‐stakeholder organizations that define processes for making decisions, sharing information, engaging the public, and resolving disputes.